PERENCANAAN STRATEGIS PENDIDIKAN BERBASIS AGAMA, FILSAFAT, PSIKOLOGI, DAN SOSIOLOGI - Arbainsyah; Ahd. Fauzi; Muhammad Al Mighwar; Ujang Nurjaman (Fakultas Agama Islam Universitas Wiralodra, 2022)
The purpose of this research is to describe and analyze the what, why, and how of strategic planning of education based on religion, philosophy, psychology, and sociology. In this study it was found that educational strategic planning is a plan for achieving 5 or 7 year goals of a systematic learning which with: (1) based on religion means being inspired by the belief in God's teachings that command careful planning, by preparing and investing potential resources, adjusting abilities, oriented to win the struggle and the general welfare, saving, and determining output and outcome; (2) based on philosophy means being inspired by academic knowledge about the cultural values of the nation, with a divine, humane, united, populist, and socially just perspective; (3) based on psychology means that which is inspired by the science of thought and behavior, especially the development of human cognition, through the stages of knowledge, understanding, application, analysis, synthesis, and evaluation; and (4) based on sociology means that it is inspired by social science about symbolic interaction, through the stages of symbol meaning, acting and interacting differently, modifying meaning, choosing meaning, determining different actions and groups.